Food Self-sufficiency Decision Support Model Based on Provinces in Indonesia Using the Clustering Method. (August 2019) - Safii, M.; Wahyudi, Mochamad; Solikhun,; Zarlis, Muhammad; Effendi, Syahril
Abstract: In Indonesia rice is a staple food as a major source of carbohydrates. Rice is also a staple food of the people of most countries in Asia and even most of the population in the world. Food security for Indonesia is closely linked to the adequacy of rice provision. The indicators of national food security are (1) the availability of food every time; (2) the ability or purchasing power of the people towards food; (3) guarantee of distribution and supply of food; and (4) the ability to import in urgent conditions. Rice as a rice-producing crop is a very important commodity for Indonesia, besides being the main food producer, rice commodity is also the main source of income from millions of farmers. The availability of rice at affordable prices to communities is an important factor for national security, security and stability. Indonesia has a large population, the fourth largest in the world after China, America and India. Dependence on rice imports has a high risk not only of food dependency on other countries, but also limited availability of rice in the international market. In 1977 Indonesia imported 2 million tons of rice and accounted for one third of the rice available on the international market, affecting the price of rice. Increased rice production can be achieved through increased productivity with the application of technology varieties and better cultivation and expansion of planting areas with increased intensity of planting and printing or opening of new rice cultivation area. Based on the above explanation, the researcher uses Data Mining Clustering with K-Means to get the assessment result of all rice production provinces. With this method the results of the research can be used as a model of decision makers for the government to give priority attention to areas that have the potential to increase rice production.